Immunohistochemical detection of receptors for oestrogen and progesterone in endometrial glands and stroma during the oestrous cycle in Nelore (Bos taurus indicus) cows - Martin, I. [UNESP]; Torres Neto, R. [UNESP]; Oba, Eunice [UNESP]; Buratini, J. [UNESP]; Binelli, M.; Laufer-Amorim, R. [UNESP]; Ferreira, João Carlos Pinheiro [UNESP] (Wiley-Blackwell, 2008)
The aim of the present study was to monitor endometrial distribution and concentrations of oestrogen receptors alpha (ER alpha) and progesterone receptors (PR) by immunohistochemistry in Nelore cows (Bos taurus indicus) during the oestrous cycle. Blood samples were collected for progesterone measurement and endometrial samples were taken from the uterine horn contra lateral to the corpus luteum in 16 cows at days 0 (ovulation), 5, 9, 13 and 19 of the oestrous cycle. Immunostaining evaluation for ER alpha and PR in the glandular epithelium and uterine stroma was performed by two methods: positive nuclei counting and staining intensity of the nuclei. Specific positive staining reactions for both receptors were limited to cell nuclei and they were not identified in the cytoplasm. The proportion of ER alpha positive nuclei had a temporal variation throughout the oestrous cycle in both cell types evaluated and was higher in uterine stroma than the glandular epithelium (p < 0.05). The greatest proportion of ER alpha stained nuclei was observed at oestrus and during the initial and mid luteal phase (days 5, 9 and 13) (p < 0.05) in the glandular epithelium and at days 0, 5 and 9 in the uterine stroma (p < 0.01). The proportion of PR positive nuclei remained constant throughout the entire oestrous cycle for both cell types evaluated (p > 0.05). A higher proportion of PR positive nuclei was measured in the uterine stroma compared with the glandular epithelium (p < 0.05). Intensity of staining for ER alpha and PR varied throughout the oestrous cycle (p < 0.01). There was a higher staining intensity at days 0 and 5 in the stroma for ER alpha (p < 0.01) and PR (p < 0.01) and in the glandular epithelium at days 0, 5, 9 and 13 for ER alpha (p < 0.01) and at days 0, 5 and 9 for PR (p < 0.01) when compared with the other evaluated days. These data demonstrate that ER alpha and PR expression varied throughout the oestrous cycle in Nelore cows, in general with highest concentrations at oestrus and the lowest during the luteal phase. This is similar to patterns observed in Bos taurus taurus.